Bedside Teaching and Its Alternatives in the COVID-19 Pandemic - Manijeh Tabrizi; Seyyedeh Azade Hoseini Nouri; Afagh Hasanzade Rad; Setila Dalili; Seyede Tahoura Hakemzadeh; Amir Mohammad Ghanbari; Reza Bayat; Amir Reza Mashaei; Nazanin Medghalchi; Kamyar Khosravi (Mazandaran University of Medical Sciences, 2023)
Background: Bedside teaching is a concentrated form of small-group teaching that takes place in the presence of the patient. Improvement in communication skills in a sympathetic manner with the patient and the ability to provide a purposeful history description and earning skills in clinical examinations is a goal that can only be achieved at the patient's bedside. Bedside teaching has declined in recent years despite all its benefits; however, there are strong recommendations to continue this teaching modality for its valued benefits. In this context, we aimed to deal with the importance of bedside teaching and the challenges ahead in the covid epidemic as well as its alternatives for teaching medical students.  Evidence acquisition: This study was conducted through a literature search on articles in English with the relevant keywords ((((((("students, medical"[Mesh]) AND ("COVID-19"[Mesh])) AND ("education"[Mesh])) AND ("patient-centered care"[Mesh])) AND ("patient care team"[Mesh])) OR ("teaching rounds"[Mesh])) OR ("education, distance"[Mesh])) AND ("Physical examination"[Mesh]) using PubMed, Scopus, Web of Sciences, Cochrane, and Embase databases from 2001 to 2022. Results: In our search, 22 related articles were found, 3 of which were clinical trials) and 4 were review articles. This study summarized the following important issues related to bedside teaching: 1- We discussed the definition, importance, benefits, and difficulties of bedside teaching on the way to education; 2- We deliberated the causes of reluctance to carry out education at the bedside and the ways to deal with the reduction of its implementation; 3-we also noticed alternative methods for medical education in periods of special contact restrictions with patients such as the COVID-19 epidemic in this review. Conclusions: Bedside teaching has a fundamental role in medical education. In particular circumstances, such as covid 19 epidemy, in which the bedside teaching courses were suspended, it is necessary to allocate other educational arrangements and design a distance learning curriculum, including virtual teaching, uploading videos to view clinical procedures on social media platforms, interview with a virtual patient, and simulation.